Satisfaction of patients received in emergencies in the department of obstetrics and gynecology at the Yalgado Ouedraogo teaching hospital: comparative study before and after the introduction of free care - Zamané, Hyacinthe; Kiemtoré, Sibraogo; Kain, Paul Dantola; Ouédraogo, Lydie Zounogo; Thiéba, Blandine Bonané (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The quality of care perceived by the users of health care services is an important indicator of the quality of care. The aim of this study was to assess the satisfaction of patients received in obstetric and gynecological emergencies department of Yalgado Ouedraogo Teaching Hospital before and after the introduction of free care. Methods: This was a cross-sectional investigation. Data collection was carried out from February to July 2016, covering the last three months before the start of free care and the first three months of implementation of this free policy in Burkina Faso. Results: A total of 620 patients formed the sample. The reception (p=0.0001), the waiting period (p=0.0001), respect for treatment schedules (p=0.0001), respect for intimacy (p=0.0001), communication between providers and patients (p=0.007), the comfort of the delivery room (p=0.003) and the comfort of the ward room (p=0.002) were more favorably appreciated by patients before the free treatment than during that period. Overall patient satisfaction was better before the effectiveness of free care (p=0.003). Conclusions: The realization of free care process was followed by a lower patient’s satisfaction reflecting an alteration in the quality of health care services. A situational analysis of this free health care process is necessary in order to make corrective measures. Also adequate preventive measures should be adopted before any implementation to a larger scale of this free policy.